El plan de marketing en la productividad de la industria láctea de pequeños agroproductores del cantón Latacunga. - Alvarez Vicent, Diana Gabriela (2021)
This research aims to determine the relationship between the marketing plan and the productivity of the dairy industry of small agro-producers in Latacunga canton. Currently, several producers and processors have presented an economic contraction due to the Covid-19 pandemic; the small agricultural producers in the canton are concerned about the oversupply of milk. They do not apply the innovation that supposes the increase of productivity; the innovation must be connected to the marketing. The paradigm of the research is quantitative, allowing to test hypotheses that are based on numerical values and statistical analysis to establish patterns and verify theories; the level that this work takes is the association of variables, it is worth mentioning that it went through an exploratory field where a preliminary investigation was carried out, it also went through a descriptive field, where the population was observed, and the sample was obtained, and finally by the association of variables using the chi-square statistic of independence; then, it could be observed that there is a relationship. The technique used to extract the required information from the different businesses was the survey; using the Likert rating scale method, the survey was applied to the sample obtained from the total population through the parish government. The SPSS program was used to organize the data because it facilitated the interpretation of the information, allowing statistical calculations and analyses to be carried out and thus facilitating decision-making. The results showed a relationship between the indicators of the variables of the marketing plan and productivity, showing that it is associated with the performance of small agricultural producers.